1965
DOI: 10.1113/expphysiol.1965.sp001796
|View full text |Cite
|
Sign up to set email alerts
|

THE EFFECT OF HYPERTHERMIA ON THE SYSTEMIC AND PULMONARY CIRCULATION OF THE OX (Bos taurus)

Abstract: The cardiac output, arterial blood pressure, pulmonary arterial pressure, heart rate, blood volume, respiratory rate and rectal temperature of the unanaesthetized ox have been measured at environmental temperatures of 150 C. and 400 C. (low humidity) and also during hyperthermia induced by increasing the humidity of the hot environment (400 C.). Derived values for total peripheral resistance, central blood volume and cardiac work were obtained from the measured data.The cardiac output, central blood volume and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
35
1

Year Published

1966
1966
2001
2001

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 21 publications
(29 reference statements)
5
35
1
Order By: Relevance
“…Some studies reported an increase in cardiac output in man (Rowell, 1974(Rowell, , 1983, dog (Hales & Dampney, 1975), ox (Whittow, 1965), or chicken (Whittow et al 1964) exposed to high ambient temperatures, whereas no change was observed in the baboon (Hales et al 1979) or sheep (Hales, 1973a). It is of importance to note that those experiments were all performed with animals under acute heat stress, which differs from our study performed with warm-acclimated pigs.…”
Section: Discussioncontrasting
confidence: 60%
“…Some studies reported an increase in cardiac output in man (Rowell, 1974(Rowell, , 1983, dog (Hales & Dampney, 1975), ox (Whittow, 1965), or chicken (Whittow et al 1964) exposed to high ambient temperatures, whereas no change was observed in the baboon (Hales et al 1979) or sheep (Hales, 1973a). It is of importance to note that those experiments were all performed with animals under acute heat stress, which differs from our study performed with warm-acclimated pigs.…”
Section: Discussioncontrasting
confidence: 60%
“…Our results confirm those of Symbas et al (1964), who found an increase in total plasma catecholamine concentration when the rectal temperature of anaesthetized dogs had risen to 40.50 C, although the catecholamine levels they reported were very much higher than those recorded here. The plasma volume of the ox decreases during hyperthermia, the mean decrease amounting to approximately 10 % (Whittow, 1965). It is apparent from the magnitude of the increases in plasma catecholamine concentration observed in the present experiments that such haemo-concentration could not be the main factor causing an increase in the plasma catecholamine levels.…”
Section: Resultssupporting
confidence: 44%
“…The mean respiratory rate increased to a maximal value at a rectal temperature of 40-5°C and slowly declined at higher rectal temperatures, although there was no significant difference in the mean respiratory rate measured at rectal temperatures of 40.50 and 41-5' C. This pattern of respiratory activity during hyperthermia in the ox has been observed before (Findlay, 1957;Bianca & Findlay, 1962;Ingram & Whittow, 1962b;Whittow, 1965). Analysis of variance indicated that the variation in plasma adrenaline levels associated with hyperthermia was statistically significant at the 0 1 % level.…”
Section: Resultsmentioning
confidence: 72%
See 2 more Smart Citations